2017
DOI: 10.1021/acsbiomaterials.7b00325
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Based Nanobiohybrid Thin Film for Amperometric Glucose Sensing

Abstract: This pioneering study involved the fabrication of a new class of nanohybrid-based electrochemical glucose biosensor. First, three-dimensional (3D) graphene was fabricated as a platform of multiwalled carbon nanotube (MWCNT). Then, it was used to immobilize glucose oxidase (GOD) on nanohybrid thin film via the entrapment technique. The modified glucose biosensor indicated excellent biocatalytic activity toward the glucose measurment with a sensitivity of up to 49.58 μA mM–1 cm–2 and a wide linear dynamic range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…These results suggest that the bio-nanoink prevents leaching and contamination of Ata GDH and SWCNT components. Table shows a comparison of the characteristics and performances of the biosensor fabricated by bio-nanoink are compared with those for other glucose biosensors. It is confirmed that the present sensor with the DET bio-nanoink exhibited better performance compared with most of the other enzyme glucose biosensors. Although there may be some better and simpler sensors in literature than the proposed one, these use glucose oxidase, which is a disadvantage because enzyme-catalytic reaction depends strongly on the concentration of dissolved oxygen at higher glucose concentration.…”
Section: Results and Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…These results suggest that the bio-nanoink prevents leaching and contamination of Ata GDH and SWCNT components. Table shows a comparison of the characteristics and performances of the biosensor fabricated by bio-nanoink are compared with those for other glucose biosensors. It is confirmed that the present sensor with the DET bio-nanoink exhibited better performance compared with most of the other enzyme glucose biosensors. Although there may be some better and simpler sensors in literature than the proposed one, these use glucose oxidase, which is a disadvantage because enzyme-catalytic reaction depends strongly on the concentration of dissolved oxygen at higher glucose concentration.…”
Section: Results and Discussionmentioning
confidence: 63%
“…This characteristic is often observed at the other biosensors. [2][3][4]8,9 It does not affect the accuracy of quantification. The effects of the interfering compounds Lascorbic acid (AA) and uric acid (UA) on the sensing characteristics are negligible (bottom inset of Figure 7A), suggesting that the biosensor fabricated by bio-nanoink can be used with physiological samples.…”
Section: Acs Omegamentioning
confidence: 99%
See 1 more Smart Citation
“…The diversity of carbonic structures does not end at the fullerene, carbon nanotubes, and graphene. , Nowadays, the fabrication of hollow and porous carbon nanostructures, produced via carbonization of organic materials, is extensively progressing. Well-defined pore structures, remarkably high surface areas, extremely short mass diffusion and transport resistance, and precisely tuned pore sizes are some highlighted features of hollow carbon structures .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, graphene-based materials have garnered attention for sensing applications due to their biocompatibility and conducting nature. Chen et al, reported few CNT-graphene based composite materials, such as GO-MWCNT hybrid, electrochemically reduced rGO-MWCNT, and Au nanoparticle-decorated graphene-CNT hybrid. Other graphene-based composites that have been reported in the literature for GOx immobilization include a graphene-CNT hybrid film grown by 3D seamless chemical vapor deposition, PDDA-capped Au nanoparticles incorporated on functionalized graphene-MWCNT nanocomposite, a 3D graphene layer as a platform for GOx-MWCNT composite immobilization, and rGO-CNTs-carbon fiber felt-based electrode . Although these CNTs based electrode materials have shown reasonable sensitivity, they suffer from some several drawbacks such as cumbersome methodology to fabricate the electrode film and requirement of expensive chemicals, surfactants, ionic liquids, and polymers as well as Pd, Pt, Au, and Ag metal nanoparticles that require extensive procedures made to activate modified electrode.…”
Section: Introductionmentioning
confidence: 99%